Usklajevanje delovnih in družinskih obveznosti v vojaški organizaciji - Juvan, Jelena (Socialno delo, 2009)
The reconciliation of work and family demands is not a novel concept and has been present since people started being employed outside their homes. It became more acute in the second half of the twentieth century, when women first entered labour market. In spite of all changes, the family is still believed to be an exclusively female domain, and women's engagements in it have a primacy.Military organization is a traditional 'male' organization. The gender dimension of the discussed topic is thus very strong and should not be ignored. It becomes even more apparent when reconciliation of demands from 'male' military organization and 'female' family is an issues.Both institutions must find a way of cohabitation in order to avoid a conflict that can be useful to neither of them.
Keywords: delo; labour; družina; family; vojaški poklici; obveznosti